2006
DOI: 10.1002/lsm.20374
|View full text |Cite
|
Sign up to set email alerts
|

Monopolar radiofrequency tissue tightening—how we do it in our practice

Abstract: Monopolar radiofrequency technology plays a unique and well-defined role in our practice. Strict patient selection in conjunction with detailed, honest, informed consent are the keys to successful treatments and patient satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…However, the results of non-ablative resurfacing are often variable and unpredictable, with some patients showing little or no response, and this is seen too in radiofrequency technology (6,14). It is estimated that up to 30% of patients see no improvement with monopolar radiofrequency and patients should be clearly counseled about the unpredictability of the procedure (15). It has been suggested that younger patients may respond better compared with older patients (6,12,14) and this may be due to the fact that heat-labile collagen bonds are progressively replaced by irreducible multivalent cross-links as the skin ages, thus rendering older skin less amenable to heat-induced tissue tightening (14).…”
Section: Discussionmentioning
confidence: 98%
“…However, the results of non-ablative resurfacing are often variable and unpredictable, with some patients showing little or no response, and this is seen too in radiofrequency technology (6,14). It is estimated that up to 30% of patients see no improvement with monopolar radiofrequency and patients should be clearly counseled about the unpredictability of the procedure (15). It has been suggested that younger patients may respond better compared with older patients (6,12,14) and this may be due to the fact that heat-labile collagen bonds are progressively replaced by irreducible multivalent cross-links as the skin ages, thus rendering older skin less amenable to heat-induced tissue tightening (14).…”
Section: Discussionmentioning
confidence: 98%
“…Noninvasive skin tightening devices have become increasingly popular over the last decade to improve skin laxity with minimal risk and recovery time (Burns & Holden, 2006;Carruthers, Fabi, & Weiss, 2014). The Thermage ® system (Solta Medical Inc., Hayward, CA) is a non-ablative device that uses monopolar radiofrequency (RF) to tighten the skin (Abraham & Mashkevich, 2007;Sukal & Geronemus, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The organ where the first signs of aging become visible is the skin 13 . Non‐ablative techniques such as radiofrequency, which do not cause pathological alterations in the skin and whose ability to be reduce wrinkles, have been demonstrated 14,15 . Our work focuses on the use of bipolar radiofrequency and uses as model the rat tail, which is rich in connective tissue.…”
Section: Discussionmentioning
confidence: 99%